Analisis Pengaruh Kapabilitas Pengguna, Program Pendidikan/pelatihan Serta Dukungan Teknologi terhadap Kinerja Sistem Informasi Akuntansi Pada CV. Wijaya Abadi Bersama - Bagus Kusuma Ardi; Risky Yunica Permata Sari; Batista Sufa Kefi (AKUNTANSI 45, 2026)
This study aims to analyze the influence of personnel capabilities, education and training, and technological support on the performance of accounting information systems (AIS). The research was conducted using a quantitative approach to examine the relationships between the independent variables and AIS performance. The population consisted of 60 employees, while a sample of 30 respondents was selected using a purposive sampling technique based on predetermined criteria. Data were collected through questionnaires and analyzed using multiple linear regression to determine the effect of each independent variable on the dependent variable. Prior to hypothesis testing, validity and reliability tests were conducted to ensure the quality of the research instrument, and the results showed that all questionnaire items were valid and reliable. In addition, the regression model met the required assumptions and demonstrated a good model fit. Hypothesis testing was carried out at a 5% significance level. The findings indicate that personnel capabilities have a significant positive effect on AIS performance. Likewise, education and training significantly improve AIS performance, while technological support also has a significant positive influence on the effectiveness of accounting information systems. Therefore, all three proposed hypotheses are accepted.